Adrenarca y función Hipotálamo-Hipófiso-Gonadal (HHG) en pacientes nacidos pequeños para edad gestacional (PEG) en función de la caracterización molecular del gen del Receptor de Hormona de Crecimiento (GHRd3/d3, GHRd3/fl, GHRfl/fl) en población Argentina - Pujana Pentreath, Matías (2019)
The Growth Hormone Receptor (GHR) mediates the action of Growth Hormone (GH) on growth and metabolism. In humans, GH is secreted by the pituitary gland and acts directly on the GHR in various cell types, generating an increase in the expression of the Insulin Like Growth Factor-1 (IGF1) as well as other genes dependent on GH.\nActually, the GHR gene is widely studied and characterized. It is located on the short arm of chromosome 5 and consists of 9 coding exons (exons 2 to 10) and 1 non-coding exon. This receptor presents an extracellular domain involved in the dimerization and binding of GH (exons 3 to 7), a transmembrane domain that binds the receptor to the cell surface (exon 8) and an intracellular domain involved in signaling by activating the via JAK-STAT (exons 9 and 10). This gene encodes for GHR, a protein that consists of 638 amino acids. Through the activation of the receptor, growth hormone is involved in a large number of physiological processes in different cell types. The biological actions of the GH can include two groups: Those of direct type (that do not require mediators) as their actions on the growth cartilage, hydrocarbon and lipid metabolism; and those of indirect type (mediated by insulin-like growth factors or IGFs) as a large part of the action on growth and protein and hydrocarbon metabolism.\nSeveral polymorphisms associated to the GHR gene have been described, being one of the most frequent the deletion of the complete exon 3 of the gene (GHRd3), which generates the loss of 22 amino acids and the A24D substitution in the N-terminal end of the extracellular domain of the receptor. The genotypic frequency of this polymorphism was analyzed in several studies and in various human populations, reporting frequencies from 2-27% in homozygosis and 15-60% in heterozygosis depending on the population under study. Although there are significant variations between the different populations, in all cases it is a frequent variant. Since its discovery to date, this polymorphism has been widely studied, as it is found in a highly conserved site in different mammalian species and consists in the deletion of a complete exon without affecting the function of the protein or its affinity for the growth hormone. These characteristics suggest that it could play an important role in adaptive mechanisms, in growth and in the response to pharmacological treatment with growth hormone.\nThere is large evidence to support the theory that this polymorphism is involved in several clinical aspects related to growth, hydrocarbon metabolism and puberal development.\nOBJECTIVES:\n- Development of a previously described technique to detect both alleles of the GHR gene (GHRfl and GHRd3).\n- Study the allelic frequency of the GHRd3 polymorphism in our population.\n- Analyze the genotypic variants of the GHR gene (GHRd3/d3, GHRd3/fl, GHRfl/fl) and its relationship with growth in SGA children, as well as with the early onset of adrenarche, the activation of the HPG axis in these patients and the hydrocarbon metabolism.\n- Study the presence of exon 3 of the GHR gene in messenger RNA from different patients and correlate the results with the genotypes of these patients.\nMATERIALS AND METHODS:\nIn the present study, we analyzed 65 SGA patients and 94 patients with appropriate weight and height for gestational age (AGE). In all cases, data were obtained at birth and at the age of evaluation. The AGE patients were used to obtain the genotypic frequencies in the population.\nAll samples were analyzed by duplex PCR, using a previously described technique for the identification of GHR gene transcripts with retention (GHRfl) or exclusion (GHRd3) of exon 3. The genotypes of all patients were evaluated together with auxological data obtained at birth, at the study age and at pubertal age in those cases in which it was possible. It was considered SGA to all children with a history of intrauterine growth retardation confirmed during pregnancy control or born with a weight below -2SDS for their gestational age and gender. When gestational age was not available, SGA was considered to be a newborn with a birth weight less than 2.5kg.\nThe presence of exon 3 of the GHR gene in messenger RNA was analyzed in placental samples by an RT-PCR technique, followed by PCR, both previously described.\nRESULTS:\nThe frequency in our population was 48% for the homozygous GHRfl genotype, 38% for the heterozygous genotype and 14% for the homozygous GHRd3 genotype. They reached Hardy-Weinberg equilibrium.\nNo differences were found in the anthropometric data at birth between the homozygous groups for the GHRfl allele (GHRfl/GHRfl) and carriers of the GHRd3 allele (GHRd3/-). The proportion of SGA patients carrying the d3 allele who experienced spontaneous compensatory growth (catch-up) was greater than in the homozygous GHRfl group. The difference in height between the moment of assessment and the body length at birth (? height) was greater for the carriers of the GHRd3 variant. Other auxological parameters were not significantly different between the carriers of both genotypes.\nIGF1 and IGFBP3 values in pre-puberal patients prior to the initiation of treatment with rhGH did not show significant differences between genotypes.\nThe age of puberal onset in both sexes was similar between the carriers of the variant GHRd3 and the GHRfl. There were also no differences in the prevalence of early puberty in both groups. SDHEA values in prepuberty did not show significant differences between subgroups of GHR variants.\nThe values of glycemia, insulin and HOMA index in SGA patients without treatment with rhGH in prepuberty did not show significant differences based on the allelic variant of GHR. No differences were found in other clinical parameters such as weight and body mass index.\nIn respect to GHR expression, at the end of the study, all the placentas genotyped presented the GHRd3/GHRfl or GHRfl/GHRfl genotypes. There was not any homozygous GHRd3 placenta. In all cases, the transcripts observed perfectly match the genotype obtained, indicating that all the isoforms present in the patient's genome would be expressed in the evaluated tissue.\nCONCLUSIONS:\nThe genotypic frequency of the GHRd3 polymorphism in the study population is similar to the results obtained by different groups in other populations worldwide. Regarding growth, although no differences were observed in prenatal growth or in serum levels of IGF1, a significant variation in spontaneous postnatal growth was observed between both groups studied.\nIn our study, no significant differences were found in the age of puberal onset in women or in males according to the GHR polymorphism. There are very few research that studied this topic previously, so the evidence is poor and no large comparisons can be made, but our data can be useful as a starting point in the subject.\nRegarding the hydrocarbon metabolism, there were no differences based on the GHRd3 polymorphism. The results previously published by various authors show great controversy regarding this issue and we believe our study provides extra data to try to elucidate this topic.\nWith regards to the assays of GHR expression in healthy placentas, the results show that for each genotype, all the expected isoforms were found. This indicates in that tissue no splicing mechanism would occur to originate an isoform not present in the patient's genome. This is the first time that this study has been performed in placentas and this could explain the differences observed in the results published years ago. It is convenient to continue studying this phenomenon in order to obtain patients with a homozygous genotype for the GHRd3 allele.\nIt would be important to increase the size of the population under study in order to obtain a more representative population. This will allow a more complete analysis of the effect that the polymorphism could have on the different variables studied.